Particle agglutination assays to identify fibronectin and collagen cell surface receptors and lectins in Aeromonas and Vibrio species. - Ascencio, F (1990)
A rapid particle agglutination assay (PAA) utilizing latex beads coated with connective tissue and serum proteins was evaluated for its ability to identify fibronectin, collagen (types I and IV), fibrinogen, and transferrin cell surface receptors on Vibrio and Aeromonas strains isolated from diseased fish, human infections, and the environment. Similar tests were performed to screen for cell surface lectins. Vibrio as well as Aeromonas strains were found to bind connective tissue proteins (collagen types I, II, and IV and fibronectin), serum proteins (i.e., fibrinogen), and glycoproteins (bovine submaxillary mucin, hog gastric mucin, orosomucoid, and fetuin) immobilized on the latex particles. The specificity of the agglutination reaction was studied by particle agglutination inhibition assays performed by preincubating bacterial suspensions in solutions containing either gelatin (for the various connective tissue protein PAA reagents) or sialic acid-rich glycoproteins (for the various glycoprotein PAA reagents). Expression of cell surface receptors for connective tissue proteins was found to depend on culture methods.